Muntschick, J. (2018). The Southern African Development Community (SADC) and the European Union (EU). Regionalism and External Influence. Palgrave Macmillan, 186 p - Alexandra Alexandrovna Arkhangelskaya (Vestnik RUDN. International Relations, 2020)
-